Radiative hybrid ferrofluid flow over a permeable shrinking sheet in a three-dimensional system - Khashi'ie, Najiyah Safwa; Waini, Iskandar; Wahid, Nur Syahirah; Md Arifin, Norihan; Ioan Pop, Unfound (Akademia Baru Publishing, 2022)
Due to the significance of magnetic nanofluids in environmental and biomedical sectors, this study is designed to analyze the available solutions alongside with the flow and thermal behaviours of radiative hybrid ferrofluid flow in a three-dimensional system subjected to the shrinking surface. The case of Fe3O4-CoFe2O4/water is considered in this work. The initial procedure is conducted by reducing the complex model into a system of nonlinear differential equations using similarity transformation technique. The results are generated using the bvp4c package in the Matlab software and graphically presented. The existence of dual solutions leads to the treatment of stability analysis where the first solution is affirmed as the physical solution. Meanwhile, the impact of thermal radiation, magnetic field and suction are also observed for the distributions of thermal rate and skin friction coefficients. These distributions boost with the imposition of magnetic field and suction while a deterioration in thermal rate is observed with the rise of thermal radiation.